2019
DOI: 10.17159/sajs.2019/6410
|View full text |Cite
|
Sign up to set email alerts
|

Poultry and cattle manure effects on sunflower performance, grain yield and selected soil properties in Limpopo Province, South Africa

Abstract: The application of organic manures as alternatives to reduce the use of mineral fertilisers is considered a good agricultural practice for smallholder farmers. However, the effect of organic manure on soil properties and crop yield depends upon its application rate and its chemical composition. A field experiment was carried out during the 2013/2014 and 2014/2015 seasons at the University of Venda experimental farm (Limpopo Province, South Africa) to determine the effect of three organic manures (cattle, poult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In addition, the short duration of the experiment may also cause a decrease in the impact of organic manure on soil quality. A similar result has been reported by Mokgolo et al [ 44 ]. Rees et al [ 45 ] indicated that the application of CM improved the soil biological properties but did not change the soil organic carbon content and soil physical properties in the three-year study duration.…”
Section: Resultssupporting
confidence: 92%
“…In addition, the short duration of the experiment may also cause a decrease in the impact of organic manure on soil quality. A similar result has been reported by Mokgolo et al [ 44 ]. Rees et al [ 45 ] indicated that the application of CM improved the soil biological properties but did not change the soil organic carbon content and soil physical properties in the three-year study duration.…”
Section: Resultssupporting
confidence: 92%
“…Bhatt, et al [67] observed that maize productivity was influenced by the combination of different sources of organic and inorganic soil amendments. Studies have shown the benefits of soil amendments to crop yield, as well as improvement of soil properties [27][28][29][30]. Tahir et al [68] suggested the alleviation of plant stress through nutrient management.…”
Section: Effects Of Soil Amendment On the Maize Growth Attributes And...mentioning
confidence: 99%
“…Several studies have shown the positive effects of organic soil amendments on crop productivity and restoration of degraded soils [27][28][29][30]. However, the adoption of organic manure as a soil amendment is low among farmers in South Africa [31].…”
Section: Introductionmentioning
confidence: 99%
“…The mineralization of these organic materials releases plant-available nutrients (Jacoby et al 2017). Conversely, organic fertilizers boost soil microbial activity by providing an energy source to microorganisms and enhance plant growth by providing a broad array of nutrients (Mokgolo et al 2019;Wu et al 2020).…”
Section: Discussionmentioning
confidence: 99%